Evaluation of the distribution of dentistry specialists in Dentística in Brazil (Research, Society and Development, 2020)
The objective is to evaluate and characterize the distribution in Brazil of dentists who have registered with the Federal Council of Dentistry as specialists in Dentística ou Dentística Restauradora, providing a view of the labor market. Data were collected based on documentary research from public archives, with quantitative and percentage characterization and presentation of results in the form of descriptive statistics. Of the 333,030 dentists registered throughout the country, only 6,363 have records as specialists in Dentística ou Dentística Restauradora, corresponding to approximately 2%. Four of the five states with the lowest percentage of records in the studied specialties are from the North of the country, while the five brazilian states with the highest percentage are from the Southeast and South, with São Paulo occupying the first position. The Northeast region proportionally shows itself as the least competitive and most promising for specialists in Dentística ou Dentística Restauradora, in contrast to the Midwest region. It is concluded that the studied specialties are extremely promising, since they are essential for the development of excellent dentistry, in addition to the need to pay attention to the most favorable regions and states for the professional development of these specialists, since there are significant differences in terms of spatial distribution in the country.